The Construction of Shariah-Compliant Museum Guidelines in Malaysia (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
Nowadays, the role of museums are prominent in society. It has served as a multi-functional institution as an economic generator, custodian of heritage, carrier of the national development agenda and educational tool. All of them are directly related to efforts to dignify Islam in life. However, despite all these functions, there are still no shariah-compliant museum guidelines that museum institutions can refer to. To that end, this study will try to develop guidelines for syariah-compliant museums using two main methods. The first method is the method of content analysis of materials related to museums and Islam. The second method is the Fuzzy Delphi method, which is a method of obtaining the confirmation of museum, culture and Islamic law experts about the syariah-compliant museum guidelines that suit the Malaysian values. The results of this study will produce two sharia-compliant museum guidelines for museums in Malaysia. This guideline consists of the aspects of (a) curators and (b) museum artifacts. Both of these guidelines contain an Islamic world-view that is adapted to the current Malaysian culture and values.Full text: PDF